Keeping adults physically active after Falls Management Exercise (FaME) programmes end: development of a physical activity maintenance intervention - Sarah Audsley; Denise Kendrick; Pip Logan; Elizabeth Orton (Pilot and Feasibility Studies, 2021)
Abstract Background Falls prevention exercise programmes help to improve muscle strength, balance and physical function, and reduce falling rates in older adults. Improvements in muscle strength, balance and physical function are reversed if older adults do not continue to be physically active after falls prevention exercise programmes end. This paper describes the design process of an intervention that aimed to maintain physical activity in older adults exiting falls prevention exercise programmes. Methods The development of the Keeping Adults Physically Active (KAPA) intervention and its implementation plan was guided by Bartholomew’s Intervention Mapping approach. The intervention mapping approach involved (1) performing a needs assessment and developing intervention objectives using previous literature; (2) identifying theory-based intervention strategies from a systematic review and the National Institute of Clinical Excellence guidelines; and (3) designing the KAPA intervention and its implementation plan with the guidance from an expert steering group. Results The KAPA intervention comprised of six group sessions of motivational interviewing, delivered monthly by trained and mentor-supported falls prevention practitioners. Intervention sessions lasted up to 90 min and were delivered in community settings over a 6-month duration. Participant manuals, illustrated exercise books, physical activity diaries and pedometers supported the KAPA intervention. Conclusions The intervention development process, consisting of Bartholomew’s Intervention Mapping approach and the input from an expert steering group, was successful in creating the evidence-based KAPA intervention ready to be evaluated in a feasibility trial.